Leadership, culture, and sustainability in community college-to-medical school pathways supporting students from historically underserved populations - Freeman Savage, Tashaé M. (My University, 2026)
Students from historically underserved populations remain underrepresented in medical education, and community college–to–medical school partnerships have emerged as a strategy for expanding access. However, limited research has examined the leadership and organizational conditions that influence whether these initiatives are sustained over time. This qualitative study explored how institutional leaders at community colleges, medical schools, and intermediary organizations develop and sustain pathway partnerships that support the matriculation of students from historically underserved populations. The study also examined how institutional culture shapes leadership decision-making related to these partnerships. Guided by Schein’s (2010) Three Levels of Organizational Culture and the 10 Dimensions of a Learning Culture, this study employed a generic qualitative design. Semi-structured interviews were conducted with 12 institutional leaders across the western and southwestern United States. Data were analyzed using inductive thematic analysis. Seven themes emerged. Partnerships were often driven by individual champions rather than institutional systems. Institutional values frequently conflicted with operational admissions practices. Sustainability was constrained by reliance on external funding rather than embedded institutional structures. Accountability timelines were misaligned with long-term student pathways. Intermediary organizations served as key structural supports. Pre-health advising gaps limited access to pathway information. Partnership labor was often invisible and uncompensated. Findings suggest that sustainable pathway partnerships require formal institutionalization, including alignment with organizational priorities, development of learning-oriented cultures, and integration into institutional structures and resource allocation processes.
Keywords: Community college–to–medical school pathways; Institutional culture; Leadership in higher education; Pathway program sustainability; Medical school admissions; Cross-sector partnerships